Bladder p75NTR-Mediated Anti-Inflammatory Response via the TLR4/TRAF6/NF-κB Axis - Claudia Covarrubias; Abubakr H. Mossa; Laura R. Yan; Benjamin Desormeau; Philippe G. Cammisotto; H. Uri Saragovi; Lysanne Campeau (Life)
Recurrent bacterial cystitis in women can lead to interstitial cystitis or bladder pain syndrome (IC/BPS). Activation of Toll-like receptor 4 (TLR4) by LPS can upregulate signaling of the pro-inflammatory receptor p75NTR. The aim of the presented study was to assess whether p75NTR antagonist THX-B can modulate LPS-mediated inflammation in bladder cells. In vitro expression and LPS-activation of p75NTR were confirmed in urothelial (URO) and smooth muscle (SMC) cells. In UROs, p75NTR antagonism abolished the LPS-elicited rise in membrane-bound and soluble TNF-α. However, it could not prevent LPS-induced rise in phosphorylated ERK nor decrease in phosphorylated p38MAPK, nor the increase in iNOS and nitric oxide (NO) content. On the other hand, in SMCs, LPS increased phosphorylation of JNK, nuclear translocation of NF-κB, and association of TRAF6 to p75NTR, outcomes prevented by p75NTR antagonism. In UROs, LPS decreased the expression of tight junction proteins, ZO-1 and occludin, with the latter rescued by p75NTR antagonism. Intraurethral instillation of LPS increased inflammation in the lamina propria, activation of JNK, and contractile activity of bladder tissue. Alternatively, intraperitoneal THX-B injections prevented LPS-induced inflammation but not enhanced muscle contraction. Our results suggest that inhibition of p75NTR could help in reducing bladder symptoms during cystitis.